Relação entre abuso emocional, sintomas psiquiátricos, esquemas iniciais desadaptativos e apego adulto - Tomaz, Maria Paula Bento (2021)
Among the multiple Early Life Stress (ELS), the presence of emotional abuse has been pointed as an influencing factor for human development and psychological disorders. Despite the knowledge about the association between ELSs and mental disorders, less emphasis has been noticed on the mediating role of Early Maladaptive Schemes (EMS) and insecure attachment styles in the relationship between emotional abuse and psychiatric symptoms. This research was divided into two studies: the first study’sobjective was to investigate the possible relationships between emotional abuse, psychiatric symptoms and EMSs. The second study, on the other hand, aimed to evaluate the mediation effect exerted by insecure attachment styles on the relationship between emotional abuse and psychiatric symptoms. This research is characterized as cross-sectional, correlational and quantitative, with a sample of 200 literate people of both sexes, aged between 18 and 30 years. Data collection was performed using a sociodemographic questionnaire, the Adult Self Assessment Inventory (ASRI), the Childhood Trauma Questionnaire (CTQ), Young Scheme Questionnaire (YSQS3) and the Style Scale Relationship (AAS). The results obtained from the first study point the first and second domains (disconnection and rejection; impaired autonomy and performance) as significant mediators in the relationship between emotional abuse and psychiatric symptoms. In the second study, the results also indicate that the anxious attachment style significantly measured the relationship between emotional abuse and psychiatric symptoms, thus pointing out the impact of children's relationships on the development of specific vulnerabilities, emotional dysregulation and the appearance clinical symptoms. In this study, the presence of EMSs and the style of anxious attachment significantly increased the power of predicting psychiatric symptoms associated with emotional abuse. Thus, it is suggested that intervention in EMSs and adult attachment styles may be one of the ways to manage psychiatric symptoms.